The investigation of solutions for nonlinear system of differential equations with boundary conditions - R.N. Butris; Azzam salahdin younis (College of Education for Pure Sciences, 2007)
Abstract In this paper we investigate the existence and approximation for nonlinear system of differential equations with boundary conditions by using the numerical-analytic method for investigate of a periodic solutions which is given by Samoilenko A. M. and also these investigations lend us to the improving and extending the above method.